2020
DOI: 10.1177/0885328220941466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different exposure times on physicochemical, mechanical and biological properties of PGS scaffolds treated with plasma of iodine-doped polypyrrole

Abstract: Polyglycerol sebacate (PGS) scaffolds obtained using a leaching technique were modified with iodine-doped polypyrrole (PPy-I) in a plasma reactor in order to study the effect of exposure time on the cell viability of hDPSCs. SEM analysis showed the formation and growth of PPy-I particles as the exposure time was increased, while FTIR and XPS analysis revealed the presence of -NH- and N+ groups in the chemical composition of the surfaces, relating to the increase in the amount of PPY-I particles. The water cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, an apparent swelling was observed on the cell culture SEM images, suggesting an increment of pore space three dimensionally. Considering that PLA is hydrophobic [72,73], whereas pPPy and pPPy/I are hydrophilic [45,71], these results suggest that uncoated scaffolds maintained their pore size in culture and the cells occupied available pores, thus reflecting a decrement in pore size. On the other hand, an increment of pore size in coated scaffolds suggests a good interaction of the material within a biologic medium, which in culture absorbs water and swells producing an increase in porosity, allowing cells and nutrients to migrate throughout the porous structure.…”
Section: Morphological Characterizationmentioning
confidence: 88%
See 1 more Smart Citation
“…However, an apparent swelling was observed on the cell culture SEM images, suggesting an increment of pore space three dimensionally. Considering that PLA is hydrophobic [72,73], whereas pPPy and pPPy/I are hydrophilic [45,71], these results suggest that uncoated scaffolds maintained their pore size in culture and the cells occupied available pores, thus reflecting a decrement in pore size. On the other hand, an increment of pore size in coated scaffolds suggests a good interaction of the material within a biologic medium, which in culture absorbs water and swells producing an increase in porosity, allowing cells and nutrients to migrate throughout the porous structure.…”
Section: Morphological Characterizationmentioning
confidence: 88%
“…Pore size significantly increased in rPLA+pPPy and aPLA+pPPy/I scaffolds in culture, suggesting that these scaffolds are expanding the porous space while interacting with cells and culture media. Since pPPy and pPPy/I surfaces are hydrophilic [45,71], scaffolds may be swelling from the media water uptake, explaining the increment in pore size in culture. However, aPLA+pPPy and rPLA+pPPy/I showed no significant differences between pore size as-fabricated and in culture, as cells proliferated mainly over the surface of the scaffolds in aPLA+pPPy scaffolds.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…In contrast to inorganic fillers, also synthetic (e.g., polylactic acid (PLA) [ 80 ] ) or natural (cellulose nanocrystals, [ 52 ] ureido‐pyrimidinone [ 57 ] ) polymers or metabolic compounds like tyramine [ 84 ] have been successfully blended with PGS to improve the mechanical, hydrophilic, and degradation properties. The addition of electrically conductive compounds like carbon nanotubes, [ 88 ] aniline pentamer, [ 81,85 ] graphene, [ 86 ] or plasma polymerization of polypyrrole [ 90 ] has been investigated to create highly tunable conductive films with enhanced cell survival and attachment [ 86 ] and enhanced Schwann cells (SCs) myelin gene expression. [ 81 ]…”
Section: Fabrication Techniques For Pgs‐based Biomaterialsmentioning
confidence: 99%
“…The major focus of PGS-inspired polymers is the development of scaffold material for biological tissue engineering (Wang et al, 2002;Gao et al, 2006;Gao et al, 2007;Jeong and Hollister, 2010;Kemppainen and Hollister, 2010;Masoumi et al, 2013;Khosravi et al, 2016;Ma et al, 2016;Zhang et al, 2016;Nadim et al, 2017;Hsu et al, 2018;Wu W et al, 2019;Hu et al, 2019;Jiang et al, 2019;Xiao et al, 2019;Abudula et al, 2020;Fu et al, 2020a;Apsite et al, 2020;Fu et al, 2020b;Sencadas et al, 2020b;Jafari et al, 2020;Keirouz et al, 2020;Liang et al, 2020;Martín-Pat et al, 2020;Pashneh-Tala et al, 2020;Xuan et al, 2020;Abazari et al, 2021;Behtaj et al, 2021a;Piszko et al, 2021a;Liu et al, 2021;Rastegar et al, 2021; Frontiers in Bioengineering and Biotechnology frontiersin.org Ângelo et al, 2021;Chen et al, 2022;Fukunishi et al, 2022;Saudi et al, 2022), although many other purposes have been identified for these materials. PGS-based materials have been investigated as drug delivery systems (Sun et al, 2009;Sun et al, 2013;Yang et al, 2017;Ayati Najafabadi et...…”
Section: Introduction Of Poly (Glycerol Sebacate) (Pgs)mentioning
confidence: 99%
“…The major focus of PGS-inspired polymers is the development of scaffold material for biological tissue engineering ( Wang et al, 2002 ; Gao et al, 2006 ; Gao et al, 2007 ; Jeong and Hollister, 2010 ; Kemppainen and Hollister, 2010 ; Masoumi et al, 2013 ; Khosravi et al, 2016 ; Ma et al, 2016 ; Zhang et al, 2016 ; Nadim et al, 2017 ; Hsu et al, 2018 ; Wu W et al, 2019 ; Hu et al, 2019 ; Jiang et al, 2019 ; Xiao et al, 2019 ; Abudula et al, 2020 ; Fu et al, 2020a ; Apsite et al, 2020 ; Fu et al, 2020b ; Sencadas et al, 2020b ; Jafari et al, 2020 ; Keirouz et al, 2020 ; Liang et al, 2020 ; Martín-Pat et al, 2020 ; Pashneh-Tala et al, 2020 ; Xuan et al, 2020 ; Abazari et al, 2021 ; Behtaj et al, 2021a ; Piszko et al, 2021a ; Liu et al, 2021 ; Rastegar et al, 2021 ; Ângelo et al, 2021 ; Chen et al, 2022 ; Fukunishi et al, 2022 ; Saudi et al, 2022 ), although many other purposes have been identified for these materials. PGS-based materials have been investigated as drug delivery systems ( Sun et al, 2009 ; Sun et al, 2013 ; Yang et al, 2017 ; Ayati Najafabadi et al, 2018 ; Desai et al, 2018 ; Oklu et al, 2018 ; Zhu et al, 2018 ; Rezk et al, 2020 ; Zanjanizadeh Ezazi et al, 2020 ; Sivanesan et al, 2021 ; Torabi et al, 2021 ; Heydari et al, 2022 ; Mehta et al, 2022 ), adhesives ( Mahdavi et al, 2008 ; Tevlek et al, 2017 ; Azerêdo et al, 2022 ), sealants ( Chen et al, 2011 ), coatings ( Kim et al, 2014 ; Lin et al, 2015 ; Ji...…”
Section: Introduction Of Poly (Glycerol Sebacate) (Pgs)mentioning
confidence: 99%